Entrepreneurial leadership among headmasters in Malaysian primary schools - Kavitha Selvaraja,; Ramli Basri,; Abdullah Mat Rashid,; Arnida Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Malaysian Education Quality Standard 2010 (SKPM 2010) which has been implemented in the Malaysian education administration emphasize on creative and innovative leadership in cultivating excellence in Malaysian schools. From the literature, leadership style that has creative and innovative elements is known as entrepreneurial leadership. This survey aimed to determine Malaysian primary school teachers’ perception on headmasters’ entrepreneurial leadership level, and the difference in the levels according to school type. A total of 324 teachers from 36 primary schools in Peninsular Malaysia participated in the study. Data was analysed descriptively and inferentially. Findings show that according to the teachers, National Schools (SK) and National-type Tamil Schools (SJK(T)) headmasters practice high level of entrepreneurial leadership, while National-type Chinese Schools (SJK(C)) headmasters practice moderate level of entrepreneurial leadership. In addition, findings also revealed that the level of entrepreneurial leadership of SK and SJK(T) headmasters are significantly higher than SJK(C), and there is no significant difference in the level of entrepreneurial leadership in SK and SJK(T). The findings of this study implicates that the practice of entrepreneurial leadership is confirmed to be already in place in Malaysian primary schools. This provides a new insight as there are lack of empirical evidence related to entrepreneurial leadership in Malaysian school administration prior to this research.